Erythropoietin receptor gene polymorphism in Indian pig lines - PRAMOD, S; USHA, A P; VENKATACHALAPATHY, R THIRUPATHY (The Indian Journal of Animal Sciences, 2016)
A restriction fragment length polymorphism (RFLP) based genotyping test was developed to assess a C/T polymorphism in the regulatory region of erythropoietin receptor (EPOR) gene of pigs. Homozygous CC animals were absent in all the genetic groups studied, whereas the locus appeared fixed with T alleles in indigenous animals. The association of allelic variants with traits like litter size at birth (LSB), litter size at weaning (LSW), litter weight at birth (LWB) and litter weight at weaning (LWW) were explored in Indian Large White Yorkshire (LWY), Duroc, Indigenous Ankamali and F1 crosses between LWY boars and Ankamali sows (CB). All the populations under study had very high frequency of T alleles, with desi group being fixed with T allele. Genotypes of EPOR gene were not associated with any of the litter traits. The allele frequencies remained under HWE except in desi group.